2017
DOI: 10.1371/journal.pone.0188393
|View full text |Cite
|
Sign up to set email alerts
|

Measuring stigma affecting sex workers (SW) and men who have sex with men (MSM): A systematic review

Abstract: BackgroundStigma involves discrediting a person or group based on a perceived attribute, behaviour or reputation associated with them. Sex workers (SW) and men who have sex with men (MSM) are key populations who are often at increased risk for the acquisition and transmission of HIV and who are affected by stigma that can negatively impact their health and well-being. Although stigma was included as an indicator in the US National HIV/AIDS Strategic Plan and there have been consultations focused on adding a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 110 publications
1
66
0
4
Order By: Relevance
“…Stigma measures were asked as attributable to engagement in sex work, except for measures of physical and sexual violence. Stigma measures were informed by a systematic review of stigma metrics and were validated with data from Togo and Burkina Faso 26,62,63 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma measures were asked as attributable to engagement in sex work, except for measures of physical and sexual violence. Stigma measures were informed by a systematic review of stigma metrics and were validated with data from Togo and Burkina Faso 26,62,63 .…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between HIV and uniformed officers refusal to provide protection varies by legal status (MH p value < 0.01) with an increased odds in settings without legal specification (aOR: 1.64; 95% CI: 1.29-2.08; p value < 0.001) and criminalized settings (aOR: 1.38; 95% CI: 1.10-1.72; p value = 0.005) compared with partially legalized settings. Blackmail is associated with HIV in non-specified settings (aOR: 1.50; 95% CI: 1.37-1.65; p value: < 0.001) and criminalized settings (aOR: 1.35; 95% CI: 1.07-1.71; p value: 0.010) compared with partially legalized 27 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Median years in sex work (IQR) settings. HIV is associated with physical violence in criminalized settings versus partially legalized settings (aOR: 1.34; 95% CI: 1.11-1.62; p value = 0.002).…”
Section: Study Sample Characteristics a Total Of 7259 Female Sex Wormentioning
confidence: 99%
See 1 more Smart Citation
“…Where data are available, they are often not used in key documents and policy decisions, despite an international call to further evidence-based policies [ 14 ]. Systematic reviews conducted in the past among key populations have comprehensively identified where data exist and synthesized available data to provide estimates on a range of indicators, including HIV prevalence, HIV incidence, and population size estimates [ 5 , 6 , 14 , 18 , 19 , 25 – 30 ]. However, with rapidly evolving methods for estimating population size and HIV transmission dynamics, these estimates have become dated both in terms of age of data and their usability by key stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…This potential dual stigma-HIV and alcohol abstinence-has not yet been addressed for PWH. Although stigma is generally associated with harmful health behaviors such as injection drug use or sex work, safe health behaviors may be stigmatized [21][22][23]. Currently, there are no quantitative measures to capture alcohol abstinence stigma.…”
Section: Competing Interestsmentioning
confidence: 99%